2011
DOI: 10.3390/ijms12063648
|View full text |Cite
|
Sign up to set email alerts
|

Micro Electromechanical Systems (MEMS) Based Microfluidic Devices for Biomedical Applications

Abstract: Micro Electromechanical Systems (MEMS) based microfluidic devices have gained popularity in biomedicine field over the last few years. In this paper, a comprehensive overview of microfluidic devices such as micropumps and microneedles has been presented for biomedical applications. The aim of this paper is to present the major features and issues related to micropumps and microneedles, e.g., working principles, actuation methods, fabrication techniques, construction, performance parameters, failure analysis, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
126
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(129 citation statements)
references
References 216 publications
1
126
0
2
Order By: Relevance
“…Repeated experiments using similar chips (microfluidic chips with electrodes used for sensing) showed electrode failure to be the largest root cause of system failure in these types of devices followed by blockage and leakage. This is consistent with various other studies available in literature [16] [17] [18] [19].…”
Section: Overviewsupporting
confidence: 94%
“…Repeated experiments using similar chips (microfluidic chips with electrodes used for sensing) showed electrode failure to be the largest root cause of system failure in these types of devices followed by blockage and leakage. This is consistent with various other studies available in literature [16] [17] [18] [19].…”
Section: Overviewsupporting
confidence: 94%
“…A great number of principles and techniques is used to build microactuators [6][7][8] . They include piezoelectric 9,10 , electrostatic 11,12 , thermal [13][14][15] , electrokinetic 16,17 and many other actuation principles.…”
Section: Introductionmentioning
confidence: 99%
“…Injection time is determined by the time of pump operation and depends on the volume needed and the speed of injection. This time is approximately two seconds (with total chamber volume 200 mm 3 and effective volume of biological fluid less than 100 mm 3 ). After the assay and data conversion the chamber should be rinsed and prepared for the next assay cycle.…”
Section: Micropump Developmentmentioning
confidence: 99%
“…A review of worldwide literature on micropumps developed for biologic and medical use [Ashraf M., 2011], demonstrated that the most promising and actively investigated area is the development of mechanical piezoelectric pumps.…”
Section: Microcapsule Transducers (Micropumps)mentioning
confidence: 99%